Cutaneous small vessel vasculitis following calcium-hydroxyapatite filler: A rare case report - Ghassan Barnawi; Sarah Kashkari; Arieh Gomolin; May Chergui; Badia Issa-Chergui; Lisa Iannatone (SAGE Open Medical Case Reports)
This case report describes a 61-year-old female who developed cutaneous small vessel vasculitis following a calcium-hydroxyapatite-based filler injection. The patient presented with a generalized purpuric and petechial rash, along with arthralgia. A skin biopsy confirmed features consistent with cutaneous small vessel vasculitis. Treatment with a 6-week prednisone taper resulted in complete symptom resolution. This observation warrants further investigation into the potential role of dermal fillers in triggering inflammatory conditions like cutaneous small vessel vasculitis.